EFFECTIVE STRATEGIES FOR TEACHING ENGLISH AS A FOREIGN LANGUAGE (EFL) - Bekchanova Xushbaroy (Bright Mind Publishing, 2025)
This paper explores a range of effective strategies for teaching English as a Foreign Language (EFL), emphasizing communicative competence, task-based learning, technological integration, and learner-centered pedagogy. It examines the current pedagogical frameworks and suggests practical ways to enhance learner motivation, autonomy, and long-term retention. By integrating findings from academic research and practical teaching experiences, the paper presents a holistic approach to language instruction that addresses both the cognitive and affective needs of learners. The overarching argument is that dynamic, interactive, and personalized instruction methods lead to more effective English language acquisition.